2018
DOI: 10.1155/2018/1278392
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oryzanol Treats Obesity‐Induced Kidney Injuries by Modulating the Adiponectin Receptor 2/PPAR‐α Axis

Abstract: The kidney is an important organ in the maintenance of body homeostasis. Dietary compounds, reactive metabolites, obesity, and metabolic syndrome (MetS) can affect renal filtration and whole body homeostasis, increasing the risk of chronic kidney disease (CKD) development. Gamma oryzanol (γOz) is a compound with antioxidant and anti-inflammatory activity that has shown a positive action in the treatment of obesity and metabolic diseases. Aim. To evaluate the effect of γOz to recover renal function in obese ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
1
21
1
1
Order By: Relevance
“…SREBP-1 is responsible for fatty acid synthesis, and PPAR α regulates lipid oxidation utilization [3]. It has been reported that the expression of PPAR α in kidney tissue is downregulated in the mouse model of high-fat diet and cases of stage IV of diabetic nephropathy [30, 31], which is inconsistent with our results. One of the possible reasons for inconsistency may be that the modeling time of ORG mice is about 12 weeks and the renal lesion seems to maintain in the early stage.…”
Section: Discussioncontrasting
confidence: 98%
“…SREBP-1 is responsible for fatty acid synthesis, and PPAR α regulates lipid oxidation utilization [3]. It has been reported that the expression of PPAR α in kidney tissue is downregulated in the mouse model of high-fat diet and cases of stage IV of diabetic nephropathy [30, 31], which is inconsistent with our results. One of the possible reasons for inconsistency may be that the modeling time of ORG mice is about 12 weeks and the renal lesion seems to maintain in the early stage.…”
Section: Discussioncontrasting
confidence: 98%
“…Body weight was measured weekly. After euthanasia, the fat deposits (visceral (VAT), epididymal (EAT) and retroperitoneal (RAT) were used to calculate the adiposity index (AI) by the following formula: [(VAT + EAT + RAT)/FBW] x100 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Natural compounds as γOz, the main bioactive from rice bran and germ, is a compound with anti-inflammatory and antioxidant activities [ 18 ]. Studies have shown that the γOz has a positive action in the treatment of some obesity- related comorbidities and attenuation of proinflammatory cytokines [ [19] , [20] , [21] , [22] ]. However, little is known about the γOz action as a possible agonist of PPAR-γ.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the AGING APN-mediated prostacyclin-PPARα-heme oxygenase-1 signaling pathway protects against renal ischemia/ reperfusion injury [55]. Furthermore, it has recently been shown that γ-oryzanol improves obesity-induced nephropathy by regulating the AdipoR2/PPAR-α axis [56]. Recent evidence has shown that AdipoR2-induced activation of PPARα upregulates the genes involved in fatty acid transport and binding and also activates peroxisomal and mitochondrial fatty acid β-oxidation, thereby promoting fatty acid catabolism.…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%